Daya Terima Pangsit Ayam Substitusi Tepung Kacang Lentil Merah dan Jamur Tiram sebagai Snack Remaja Overweight - Nasywa Aprilianti; Annis Catur Adi (Yayasan Literasi Sains Indonesia, 2026)
Overweight in adolescents is a serious nutritional problem with a national prevalence of 32.8% in Indonesia. One contributing factor is the high consumption of snacks with elevated fat content and low dietary fiber. This study aimed to analyze the effect of red lentil flour and oyster mushroom substitution on the hedonik acceptability and nutritional content of chicken wonton as a high-fiber, low-fat snack alternative for overweight adolescents. This study used an experimental design with a Completely Randomized Design (CRD) approach involving three formulas: F0 (kontrol), F3, and F4. Hedonik tests were conducted by 30 semi-trained panelists aged 16–18 years, evaluating taste, color, aroma, and texture. Data were analyzed using the Shapiro-Wilk, Friedman, and Wilcoxon Signed-Rank tests. Results showed that substitution significantly affected taste (p = 0.003), while color, aroma, and texture showed no significant differences. All formulas remained in the